Transient minimum creep of a γ′ strengthened Co-base single-crystal superalloy at 900 °C. (1st July 2017) - Zhou, H.J.; Chang, H.; Feng, Q.
Abstract: A characteristic creep behavior, with a transient minimum creep rate region, was exhibited in a Co-Al-W-Ta-Ti single-crystal superalloy at 900 °C and 420 MPa. Interrupted creep tests were performed at various creep regions, the investigation of substructural evolution indicated the configurations of stacking faults were different during various creep regions. The extension of stacking faults and the formation of Lomer-Cottrell locks are hypothesized to be responsible for the accelerating region and steady-state region, respectively. Graphical abstract: